Analisis Volatilitas Harga Daging Sapi Sebelum Sampai Dengan Sesudah Hari Besar Agama di Kota Jambi - Firmansyah Firmansyah; Afriani H; Wahyu Aji Paiso (Universitas Batanghari Jambi, 2021)
This study aims to analyze the level of beef price volatility before fasting (D-7) to after Eid (H + 7) in Jambi City, and compile a forecast model. This study used a survey method for beef traders in the Angso Duo market, Jambi City. The analysis used to calculate the volatility of beef prices is the ARCH (Autoregressive Conditional Heteroscedastic) model analysis and the GARCH (Generalized Autoregressive Conditional Heteroscedasticity) model analysis. The average price of beef during the period before fasting (D-7) to after Eid (H + 7) in Jambi City was IDR 124,147 per kg with the highest price of IDR 150,000 and the lowest was 110,000 per kg. The volatility of beef prices during the period before fasting (D-7) to after Eid (H + 7) in Jambi City is the highest before Eid al-Fitr (Eid). ARCH and GARCH models can predict the future value of beef prices.